1988
DOI: 10.1021/bi00408a013
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid coordinate regulation of type I procollagen gene expression and procollagen DNA-binding proteins in chick skin fibroblasts

Abstract: Nuclei were isolated from control and dexamethasone-treated (2 h) embryonic chick skin fibroblasts and transcribed in vitro. Nuclei isolated from dexamethasone-treated fibroblasts transcribed less pro alpha 1(I) and pro alpha 2(I) mRNAs but not beta-actin mRNA. Fibroblasts receiving dexamethasone and [5,6-3H]uridine also demonstrated decreased synthesis of nuclear type I procollagen mRNAs but not beta-actin mRNA. In fibroblasts treated with cycloheximide the newly synthesized nuclear type I procollagen mRNA sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The mechanisms of action are not exactly established. It has been proved that glucocorticoids suppress procollagen gene expression and they also inhibit collagenases belonging to the family of matrix metalloproteinases, which are involved in the degradation of collagen (24,(27)(28). Concerning the possible induction of the hepatic clearance pathway for the propeptides studied here, it has been shown earlier that glucocorticoids do not affect the hepatic clearance of the aminoterminal propeptide of type III collagen (24).…”
Section: Discussionmentioning
confidence: 71%
“…The mechanisms of action are not exactly established. It has been proved that glucocorticoids suppress procollagen gene expression and they also inhibit collagenases belonging to the family of matrix metalloproteinases, which are involved in the degradation of collagen (24,(27)(28). Concerning the possible induction of the hepatic clearance pathway for the propeptides studied here, it has been shown earlier that glucocorticoids do not affect the hepatic clearance of the aminoterminal propeptide of type III collagen (24).…”
Section: Discussionmentioning
confidence: 71%
“…Several studies suggest that pro␣1(I) collagen mRNA stability is decreased by glucocorticoid treatment [Mahonen et al, 1998;Raghow et al, 1986], while others indicate that regulation is at the transcriptional level [Cockayne et al, 1988;Meisler et al, 1997]. Glucocorticoids regulate transcription positively by binding of GR to a palindromic sequence of two hexamers separated by three nucleotides, or negatively by two different mechanisms [Karin, 1998].…”
Section: Discussionmentioning
confidence: 99%
“…Hamalainen et al [391 reported a similar decrease in the stability of both type I procollagen mRNAs in the presence of cortisol. In contrast, Weiner et al [114] reported transcriptional inhibition of the a2 collagen gene by dexamethasone in an in vivo model of hepatic fibrosis, as well as in cultured hepatocytes [1151, and both Cockayne et al [18,191 and Walsh et al [1121 have similarly reported transcriptional downregulation of type I collagen by dexamethasone. Finally, in transient transfection analyses in mouse fibroblasts, dexamethasone decreased expression of chimeric a2-CAT constructs (containing mouse a2 promoter sequences from -2000 to +54) to 3 4 4 1 % of control levels [115].…”
Section: Gamma-in Terferon (Y-ifn)mentioning
confidence: 99%